Antibacterial nanohydroxyapatite/polyurethane composite scaffolds with silver phosphate particles for bone regeneration. Issue 16 (1st November 2016) - Jiang, Jiaxing; Li, Limei; Li, Kuankuan; Li, Gen; You, Fu; Zuo, Yi; Li, Yubao; Li, Jidong
Abstract: Solving the issue of infection associated with implanted bone substitutes is one of the modern challenges of the biomedical engineering field. The purpose of this study was to develop a novel porous scaffold with sufficient antibacterial activity for bone repair or regeneration. Porous nanohydroxyapatite/polyurethane (n-HA/PU) composite scaffolds containing different amounts of silver phosphate particles were prepared through the in situ foaming method. Subsequently, their physicochemical properties, antibacterial abilities, and preliminary cytocompatibilities were evaluated. The results indicated that the porosity and mechanical properties of the n-HA/PU scaffolds incorporated with Ag3 PO4 did not change significantly compared to n-HA/PU scaffold without Ag3 PO4 . The release of Ag + was time and concentration dependent, increasing with the immersion time and Ag3 PO4 percentage in the scaffolds. A continuous Ag + release can last more than 3 weeks. The antibacterial tests and cytocompatibility evaluation revealed that n-HA/PU scaffolds with 3 wt% Ag3 PO4 (n-HA/PU3) exhibit stronger antimicrobial effects as well as satisfactory cytocompatibility. The n-HA/PU3 scaffolds may hold great potential for application in the field of bone regeneration, especially for infection-associated bone defect repair.